Comparative Study Between Functional MR Urography and Renal Scintigraphy to Evaluate Drainage Curves and Split Renal Function in Children With Congenital Anomalies of Kidney and Urinary Tract (CAKUT) - Damasio, Maria Beatrice; Bodria, Monica; Dolores, Michael; Durand, Emmanuel; Sertorio, Fiammetta; Wong, Michela C. Y.; Dacher, Jean-Nicolas; Hassani, Adnan; Pistorio, Angela; Mattioli, Girolamo; Magnano, Gianmichele; Vivier, Pierre H. (Frontiers in Pediatrics, 2020)
Background: obstructive congenital anomalies of the kidney and urinary tract have a high risk of kidney failure if not surgically corrected. Dynamic renal scintigraphy is the gold standard technique to evaluatedrainage curves and split renal function (SRF). Objectives: to compare functional magnetic resonance (MR) urography with dynamic renal scintigraphy in measuring volumetric SRF and in the classification of drainage curves in patients with congenital anomalies of the kidney and urinary tract. Materials and Methods: we retrospectively collected patients with hydroureteronephrosis or pelvicalyceal dilatation at renal ultrasound, who underwent both functional MR urography and DRS within 6 months. DRS studies were evaluated by a single nuclear medicine physician with double reading. Functional MR urography renograms were blinded evaluated twice by two radiologists. The functional MR urographyintra- and inter-reading agreements and the agreement between the two imaging techniques were calculated. SRF was evaluated by Area Under the Curveand Rutland-Patlak methods. Drainage curves were classified as normal, borderline or in accumulation patterns by both the techniques. Results: fifty-two children were studied, 14 with bilateral involvement. A total of 104 kidney-urinary tracts were considered: 38 normal and 66 dilated. Considering Area Under the Curveand Rutland-Patlak for SRF, the intra- and inter-reader agreements of functional MR urographyresulted respectively excellent and good, and the two techniques demonstrated a good concordance (r2: 67% for Area Under the Curveand 72% for Rutland-Patlak). Considering drainage curves, the inter-readers agreement for functional MR urography and the concordance between the two techniques were moderate (Cohen’s k respectively 55.7% and 56.3 %). Conclusions: according to our results, there are no significant differences between functional MR urography and DRS in measuring volumetricSRF and in the classification of drainage curves in patients with congenital anomalies of the kidney and urinary tract.